Pendampingan Peningkatan Kapasitas Pemerintah Desa Melalui Manajemen Media Sosial : Pengabdian - Yulfa Nur Hidayah; Ade Putra Ode Amane; Dolbi Kunjae; Rifni Aulia Bando; Faturrahman M. Pauh (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The power of social media in society influences new forms and ways of being. The use of social media brings changes and shifts in the life of the new world. The main objective of this activity is to provide assistance in increasing the capacity of the Bunga Village Government of North Luwuk Sub-district through social media management in order to form new work patterns in the management of system-based and visual public service information. This service is expected to contribute theoretically and practically in efforts to assist in increasing the capacity of village governments through social media management. The method used is a descriptive qualitative approach with a participatory method. Village governments are directly involved, especially in social media management, and are encouraged to implement the results of the assistance on an ongoing basis. The results of the service activities show that the assistance carried out in the Bunga village government, North Luwuk sub-district, can have a positive impact on the understanding of the village government in increasing the capacity of the village government through social media management, which in turn contributes to improving the quality of social media management.